Incentives for environmental R&D - Mads Greaker; Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2011)
Since governments can influence the demand for a new abatement technology through their environmental policy, they may be able to expropriate innovations in new abatement technology ex post. This suggests that incentives for environmental R&D may be lower than the incentives for market goods R&D. This in turn may be used as an argument for environmental R&D getting more public support than other R&D. In this paper we systematically compare the incentives for environmental R&D with the incentives for market goods R&D. We find that the relationship might be the opposite: When the innovator is able to commit to a licence fee before environmental policy is resolved, incentives are always higher for environmental R&D than for market goods R&D. When the government sets its policy before or simultaneously with the innovator's choice of licence fee, incentives for environmental R&D may be higher or lower than for market goods R&D.
Keywords: H23; O30; Q55; Q58; 330; R&D; environmental R&D; innovations; endogenous technological change; Industrielle Forschung; Umwelttechnik; Innovation; Ökonomischer Anreiz; Forschungs- und Technologiepolitik; Umweltpolitik; Endogener technischer Fortschritt; Theorie